2005
DOI: 10.1074/jbc.m411760200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mitogen-activated Protein Kinase Phosphatase-1 in the Response of Alveolar Macrophages to Lipopolysaccharide

Abstract: Mitogen-activated protein (MAP) kinases are critical mediators of innate immune responses. In response to lipopolysaccharide (LPS), MAP kinases are rapidly activated and play an important role in the production of proinflammatory cytokines. Although a number of MAP kinase phosphatases (MKPs) have been identified, their roles in the control of cytokine production have not been well defined. In the present report, we investigated the role of MKP-1 in alveolar macrophages stimulated with LPS. We found that LPS tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
203
2
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(221 citation statements)
references
References 32 publications
(45 reference statements)
15
203
2
1
Order By: Relevance
“…Factors that negatively regulate MAP kinase activity, by binding to and dephosphorylating active MAP kinases, form part of the dual specificity MAP kinase phosphatase (MKP) family. Consistent with this notion, several recent investigations have shown that MAP kinase specific phosphatase-1 (MKP-1) deficiency results in enhanced and prolonged p38 and JNK activation (Nimah et al, 2005;Wu and Bennett, 2005;Zhao et al, 2005). MKPs were initially identified as early response genes (Lau and Nathans, 1985;Sun et al, 1993) and are expressed ubiquitously in response to growth factors, stress, or heat shock (Farooq and Zhou, 2004;Chi et al, 2006;Hammer et al, 2006).…”
Section: Introductionmentioning
confidence: 83%
“…Factors that negatively regulate MAP kinase activity, by binding to and dephosphorylating active MAP kinases, form part of the dual specificity MAP kinase phosphatase (MKP) family. Consistent with this notion, several recent investigations have shown that MAP kinase specific phosphatase-1 (MKP-1) deficiency results in enhanced and prolonged p38 and JNK activation (Nimah et al, 2005;Wu and Bennett, 2005;Zhao et al, 2005). MKPs were initially identified as early response genes (Lau and Nathans, 1985;Sun et al, 1993) and are expressed ubiquitously in response to growth factors, stress, or heat shock (Farooq and Zhou, 2004;Chi et al, 2006;Hammer et al, 2006).…”
Section: Introductionmentioning
confidence: 83%
“…It is expressed in response to GCs A Clark Anti-inflammatory functions of glucocorticoid-induced genes Page 18 of 53 in a wide variety of cell types including mast cells (Kassel et al, 2001), monocytes or macrophages (Abraham et al, 2006;Aeberli et al, 2006;Bhattacharyya et al, 2007;Chen et al, 2002;Zhao et al, 2005), microglia (Zhou et al, 2007), T lymphocytes , dermal, lung and synovial fibroblasts (Phillips et al, 2006;Toh et al, 2004;Yang et al, 2006), endothelial cells (Furst et al, 2007), osteoblasts (Engelbrecht et al, 2003;Leclerc et al, 2004), keratinocytes (Onda et al, 2006;Stojadinovic et al, 2006), adipocytes (Bazuine et al, 2004), lung epithelial cells (Chivers et al, 2006;Hermoso et al, 2004), airway smooth muscle cells (Issa et al, 2007) and HeLa cells (Imasato et al, 2002;Lasa et al, 2002). Typically expression is quite rapid (within one hour), sustained (up to 24 hours), requires relatively low concentrations of GC, and is blocked by the GR antagonist RU486.…”
Section: Dusp1mentioning
confidence: 99%
“…Anti-inflammatory functions of glucocorticoid-induced genes Page 19 of 53 overexpression of DUSP1 attenuates signaling of the JNK and p38 MAPK pathways and inhibits the expression of several inflammatory genes (Chen et al, 2002;Nimah et al, 2005;Zhao et al, 2005).…”
Section: A Clarkmentioning
confidence: 99%
“…Treatment of cells with POPG in addition to LPS eliminated the phosphorylation of p38, p42 ERK, JNK, and IB␣ and also abrogated the reduction in the steady state levels of IB␣. In addition to inducing phosphorylation of MAPKs and IB␣, LPS induced synthesis of MKP-1 that functions to turn off MAPKs signaling (42,43). The POPG treatment blocked the synthesis of new MKP-1, indicating that the lipid is likely to act upstream of MAPK activation rather than downstream of the process by induction of MKP-1.…”
Section: Popg Inhibits the Lps-induced Phosphorylation Of Mapk And Ibmentioning
confidence: 99%